Implementation of Occupational Safety and Health in Alas Harum Bali Tourism Destination - Negara, Ni Luh Gede Aris Maytadewi; Kusuma, Made Adhyatma Prawira Natha; Putra, I Made Yudha Kurnia (GLOBAL HEALTH SCIENCE GROUP, 2023)
Tourist safety is an important aspect in tourism activities and must receive serious attention from the management from a tourism destination. This is also one of the tourists' satisfactions with services which in turn will burden the image destinations around the world. Alas Harum Bali is a popular tourist destination that has been established since 2014. Alas Harum Bali is a greenery lush tropical rice terraced inspired. Alas Harum Bali also provides a choice of rides and attractions including extreme swing, super extreme swing, swing bed, couple swing, sky bike, giant sky bike, and flying fox. The attractions that are most in demand by tourists are the extreme and super extreme swings. Even though swing tourism activities are widely known by tourists, the management and tourists must still pay attention to the occupational health and safety procedures that are implemented. This is to prevent accidents that are certainly not desirable. This research uses a qualitative approach that is descriptive. Primary data was obtained from informants, namely workers and tourists from Alas Harum Bali. Secondary data was obtained from observations at Alas Harum Bali as well as literature, documentation and previous similar research. The results show tourist attractions in Alas Harum Bali belong to tourism activities related to adventure activities because in their implementation there are elements of challenge or test of guts, draining emotions, risks that must be anticipated, and of course there are new experiences gained from adventure tourism activities. The implementation of occupational safety and health at Alas Harum Bali is good, but needs to be improved, especially in the provision of adequate and suitable personal protective equipment, especially when there are high of visitors.